The first example of bis(indolyl)methane based hyperbranched polyurethanes: Synthesis, solar cell application and anti-bacterial and anti-oxidant properties. (October 2017) - Sathiyaraj, Subramaniyan; Shanavas, A.; Kumar, K. Ashok; Sathiyaseelan, A.; Senthilselvan, J.; Kalaichelvan, P.T.; Nasar, A. Sultan
Graphical abstract: In this article, the first example of bis(indolyl)methane based hyperbranched polyurethanes showing antibacterial activity almost equal to tetracycline, free radical scavenging activity comparable to standard ascorbic acid and good solar energy conversion efficiency were reported. Highlights: In this article, the first example of bis(indolyl)methane based hyperbranched polyurethanes as multifunctional materials. It shows antibacterial activity almost equal to tetracycline, free radical scavenging activity comparable to standard ascorbic acid. Also, it exhibits good solar energy conversion efficiency. Abstract: Two new AB2 -type blocked-isocyanate monomers containing bis(indolyl)methane moiety were synthesized via a scalable synthetic routes. Except the "A" functional groups, both of the monomers are structurally identical; one was designed with phenolic OH group (Monomer-1) and the other one was designed with alcoholic OH group (Monomer-2). The first examples of indole based hyperbranched polyurethanes were derived from these monomers in DMF and THF solvents. Blocked-isocyanate end-groups of these polymers were modified with PEG-mono methyl ether. The structures of the AB2 -type monomers and their intermediates were confirmed using FT-IR, 1 H NMR, and 13 C NMR spectroscopy. The formation of hyperbranched polyurethanes and their end-group modifications were confirmed using 1 H NMR spectra. The absolute molecular weights of the polymers were determined using SEC-MALLS technique and the values were found to be varied from 6.8 × 10 3 g/mole to 1.1 × 10 5 g/mole. The diverse functions of all the synthesised polymers were studied. Dye-sensitized solar cells (DSSC) fabricated with a polymer derived from Monomer-2 (InHBPU-5) yielded an overall energy conversion efficiency of η = 6.59% upon 1 sun illumination with visible light. Also, this polymer showed activity almost equal to tetracycline (control) toward both gram-positive and gram-negative bacterial strains. In addition, this polymer and its monomer, both exhibited good capacity for scavenging DPPH free radical.